Penggabungan Metode CRAFT dan CRNN untuk Pengenalan Plat Nomor - HUSAINI, FAKHRUDIN RIZKY; SUGENG, WINARNO (e-Proceeding FTI, 2024)
At this time the development of machine learning technology which is part of Artificial Intelligence (artificial intelligence) has been widely used to facilitate human work, such as performing character recognition on automatic license plates or Automatic License Plate Detection and Recognition (ALPR). This research was conducted with the aim of being able to perform character recognition on license plates by taking advantage of the advantages of the CRAFT method as text detection based on plate codes, police numbers, and regional codes as well as taking advantage of the advantages of the CRNN method as text recognition in each part of the area on license plates. The dataset used is a synthetic dataset created using the python library. Text recognition testing on license plates was carried out on synthetic test images and original license plate test images obtained from Kaggle.com, github.com, and images.google.com. And the model training process with synthetic datasets has produced the best model with the highest accuracy of 0.9839 and the lowest loss of 0.0414. Abstrak Pada saat ini perkembangan teknologi machine learning yang merupakan bagian dari Artificial Intelligence (kecerdasan buatan) telah banyak digunakan untuk mempermudah pekerjaan manusia, seperti melakukan pengenalan karakter pada plat nomor otomatis atau Automatic License Plate Detection and Recognition (ALPR). Penelitian ini dilakukan dengan tujuan dapat melakukan pengenalan karakter pada plat nomor dengan memanfaatkan keunggulan metode CRAFT sebagai deteksi teks berdasarkan kode plat, nomor polisi, dan kode daerah serta memanfaatkan keunggulan metode CRNN sebagai pengenalan teks pada masing-masing bagian wilayah pada plat nomor. Dataset yang digunakan yaitu synthetic dataset yang dibuat menggunakan library python. Pengujian pengenalan teks pada plat nomor dilakukan pada citra uji synthetic dan citra uji plat nomor asli yang didapat dari Kaggle.com, github.com, dan images.google.com. Dan proses training model dengan dataset synthetic telah menghasilkan model terbaik dengan akurasi tertinggi sebesar 0.9839 dan loss terendah 0.0414.